Factors Related to the Low Nutritional Status among Tuberculosis Patients - Anggraini Dwi Kurnia; Nurlailatul Masruroh; Nur Melizza (Faculty of Nursing Universitas Padjadjaran, 2020)
Tuberculosis and malnutrition are serious problems. Tuberculosis causes malnutrition that potentially lessen patients’ immunity and increase the risk for activating tuberculosis. The purpose of this study was to identify the factors related to the low nutritional status among tuberculosis patients in Malang City. This research applied a corelational study. The subjects involved were tuberculosis patients with BMI<18.5. Chi-square and Fisher Exact Test were used to analyse the identified factors. Moreover, binary logistic regression to identify factors related to the low nutritional status among tuberculosis patients in Malang City. This study found almost half of participants (46.8%) had poor family knowledge about dietary TB patients. More than half of the participant’s culture (62.5%) was abstinence. A more than half of participant (59.6%) had Moderate malnutritions. There was no significant correlation between low nutritional satus and variable of gender p=1.000, education p=0.404, family knowledge p=0.767, and culture p=0.310. The significant correlation was occupational status with p=0.043. The binary logistic regression showed that tuberculosis patient with unoccupied are 1.286 times more likely to have a low nutritional status. Occupational status was the one factor that significantly related to the low nutritional status among TB patients in Malang City.